Death Deviations – on the Perception of Extraordinary Ends of Farmed Animals - Mann, Stefan (Journal of applied animal ethics research, 2025)
This qualitative study examines the public perception of the death of farmed animals that do not die in slaughterhouses and become visible in public, be it through media or art, deviations from the agricultural production system. In the first part, it is shown that the death of farmed animals due to neglect by farmers or to predacious attacks often cause a strong degree of empathetic suffering. In the second part, it is shown how the exposure of the death of farmed animals by artists is preferably ignored if the cruelties of slaughter are displayed and is met by aggressive reactions and accusations if it cannot be ignored. In such cases, reference is made to cultural values rather than to factual arguments. It is concluded that the two categories disturb the equilibrium in which we usually keep our cognitive dissonance of meat consumption, albeit in different ways.